Metabolizable and net energy requirements for entire and immunocastrated male pigs and digestible lysine for immunocastrated males - Barcellos, Joyce (2025)
In the first chapter, the objective was to determine the metabolizable and net energy requirements for maintenance and production of entire males and immunocastrated males from 70 to 130 kg of body weight, using the factorial method. Sixty entire male pigs were randomly assigned to a performance trial with four treatments (ad libitum, 75%, 50%, and 25% of the ad libitum feed), with 12 replicates and one pig per pen. The parameters of the energy model were established using the comparative method for protein and fat deposition through the Dual-Energy X-ray Absorptiometry (DEXA) approach. Energy requirements for weight gain were determined based on body energy content and the efficiency of energy utilization for weight gain. Metabolizable energy (ME) and net energy (NE) requirements for maintenance (MEm and NEm) were 160.33 and 134.52 kcal/kg BW0.75 per day, respectively, for entire males. The efficiency of utilization of ME for NE was 0.84, estimated from the slope of the linear regression equation of retained energy as a function of metabolizable energy (ME) intake. The ratio of lean to fat mass decreased during the growth period and was more pronounced in immunocastrated males, indicating that fat retention becomes more energy-efficient as body weight increases. Entire male pigs are less demanding in net energy for gain (NEg) than immunocastrated males. The ME and NE requirements for production (MEp and NEp) were 4.498 and 3.779 kcal per kilogram of body weight for entire males, and 5.298 and 4.451 kcal for immunocastrated males, respectively. The second chapter evaluated digestible lysine (DLys) levels in the diet of immunocastrated male pigs during the finishing phase regarding performance, in vivo body composition, carcass traits, and meat quality, as well as to determine DLys requirements. Sixty immunocastrated male pigs were randomly allotted to five treatments with DLys levels of 0.55, 0.61, 0.68, 0.75, and 0.82%, respectively, in 12 replicates. Overall, performance improved in response to increasing DLys levels. Carcass yield and loin weight increased linearly (P < 0.05) with increasing DLys levels, whereas loin area (LA) showed a quadratic increase (P < 0.05). Meat quality was affected, showing a linear increase in sarcomere length, drip loss (P < 0.10), and color values a* and b* (P < 0.05), as well as changes in the chemical composition of loin chops, with a quadratic decrease for intramuscular fat and crude protein in dry matter (P< 0.05). Body composition was affected, with a linear increase in fat mass gain and a quadratic increase in bone mineral content (BMC) gain (P < 0.05); however, only total body fat gain increased significantly. The DLys requirement was estimated at 0.74% for carcass parameters (carcass yield and loin weight) using the quadratic model, and for ADG using the linear-plateau model. A daily intake of 33 g DLys/day for 1.79 kg/day of ADG, or 17.90 g DLys per kg of body weight gain, is recommended for immunocastrated male pigs housed individually during the finishing phase. Keywords: nutritional requirements; body composition; DEXA; factorial method.